Systematic review and meta-analysis of the complications of salvage total laryngectomy. Issue 1 (January 2017) - Hasan, Z.; Dwivedi, R.C.; Gunaratne, D.A.; Virk, S.A.; Palme, C.E.; Riffat, F.
Abstract: Background and objectives: Management paradigms in laryngeal cancer have shifted to "organ preservation" chemoradiotherapy protocols. In the event of treatment failure, salvage total laryngectomy remains the only curative treatment option. However a comprehensive review of the complications of this procedure has not been reported. Methods: A systematic review of the literature was performed using keywords "salvage laryngectomy" to retrieve relevant publications between January 2000 and August 2015. Results: Of the 407 articles retrieved from the literature search, 50 studies encompassing 3292 patients were included. Forty-nine studies reported pharyngocutaneous fistula which occurred in 859 patients (pooled incidence 28.9%; 95% confidence intervals 25.5–32.5%). Twenty-four studies reported complications in addition to PCF and these included wound complications (infection, dehiscence and necrosis), dysphagia, bleeding, and pharyngeal and stomal stenosis. Conclusions: Overall complication rate was 67.5%, Pharyngocutaneous fistula was the commonest complication with a pooled incidence of 28.9%.